Penyusunan Unit Pembelajaran Inquiry Based Learning Berorientasi Kemampuan Abad 21 - Feriansyah Sesunan; Abdurrahman; Novinta Nurulsari; Hervin Maulina (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The context of learning in the 21st century directs teachers to think whether they will continue to play the role of "sage-on-the-stage". In connection with teacher competencies and the implementation of inquiry-based learning (IBL), in the teaching and learning process Physics teachers should be able to make learning designs suitable for inquiry learning in the 21st century. However, the form of IBL tools compiled by Physics teachers is not yet oriented towards 21st century abilities needed by students. Based on the results and discussion, it is known that 1) high school physics teachers in Bandar Lampung already know and have knowledge of the IBL model, 2) almost all high school physics teachers have applied IBL-based science learning even though they have not fully understood each IBL syntax and are not yet oriented 21st century skills, 3) there is an increase in teacher knowledge about IBL after the implementation of technical guidance, and 4) the need for further assistance in overcoming teacher obstacles in making IBL-based learning units or devices oriented towards 21st century abilities.